FER Regulated by miR-206 Promotes Hepatocellular Carcinoma Progression via NF-κB Signaling - Ding, Wenzhou; Fan, Ye; Jia, Wenbo; Pan, Xiongxiong; Han, Guoyong; Zhang, Yao; Chen, Zhiqiang; Lu, Yiwei; Wang, Jinyi; Wu, Jindao; Wang, Xuehao (Frontiers in Oncology, 2021)
Objectives Feline sarcoma-related protein (FER) is known to play a critical regulatory role in several carcinomas. However, the exact biological function of FER in hepatocellular carcinoma (HCC) still needs to be investigated. The primary objective of this research was to investigate the unknown function and molecular mechanisms of FER in HCC. Materials and Methods The expression level of FER in HCC tissue samples and cells was examined by RT-qPCR, immunohistochemistry and western blot. Cellular and animal experiments were used to explore the effect of FER on the proliferative and metastatic capacities of HCC cells. The crosstalk between FER and NF-κB signaling was explored by western blot. The upstream factors that regulate FER were evaluated through dual-luciferase experiments and western blot assays. Results FER was overexpressed in HCC specimens and HCC cell lines. FER expression levels were positively associated with unfavorable clinicopathological characteristics. The higher the expression of FER was, the worse the overall survival of HCC patients was. The results of loss-of-function and gain-of-function experiments indicated that knockdown of FER decreased, while overexpression of FER increased, the proliferation, invasion and metastasis of HCC cells in vitro and in vivo. Mechanistically, we found that FER activated the NF-κB signaling pathway and stimulated epithelial-to-mesenchymal transition (EMT). We also found that FER was directly regulated by miR-206, and the downregulation of miR-206 was associated with proliferation and metastatic progression in HCC. Conclusions The present research was the first to reveal that a decrease in miR-206 levels results in an increase in FER expression in HCC, leading to enhanced cell growth and metastatic abilities via activation of the NF-κB signaling pathway.